Age Enfreakment in Nursing Home Drama - Anna Gaidash (Humanities)
This essay explores how the concept of enfreakment can be used to analyze older adult characters in late 1970s US American theatre, focusing on D.L. Coburn’s The Gin Game and Tennessee Williams’s This is the Peaceable Kingdom. These tragicomedies reflect societal fears and stigmas surrounding aging, linking back to the historical context of freak shows. Enfreakment intersects with themes of otherness and ableism, highlighting the sensationalism associated with freak culture. The social construction of P.T. Barnum’s freak and older adults as non-hybrids (Haim Hazan) shares common ground. Using a comparative approach and close reading, this research reveals that the fictional nursing home setting limits freedom and produces both repulsion and compassion through its residents, showcasing invective as a protocol of enfreakment.